Community Pharmacy Staff Perceptions on Preventing Alcohol and Medication Interactions in Older Adults - Zanjani, Faika (J Am Pharm Assoc (2003), 2016)
OBJECTIVES: To examine rural/urban pharmacy staff perceptions on messaging, barriers, and motivators for preventing alcohol and medication interactions (AMI) in older adults (65+ years). DESIGN: A survey was distributed through the local pharmacist association and statewide pharmacy registry in Kentucky. PARTICIPANTS: A total of N=255 responses were received from pharmacists, pharmacy technicians, and pharmacy students. RESULTS: Across rural/urban regions alike, among the AMI prevention messages provided, participants identified the most important messages to be: AMI can be potentially dangerous and life threatening, emergency rooms should be used when experiencing an AMI, and doctors and pharmacists should be consulted about AMI. The most common AMI prevention barriers indicated were stigma, costs, and low perceived risks. The most common AMI prevention motivators indicated were physical health improvement/promoting a healthy lifestyle, convenient setting, and financial incentives. CONCLUSIONS: Irrespective of geography, participants similarly rated the presented AMI prevention messages, barriers, and motivators. Using the findings, the development of an AMI prevention program is suggested utilizing messaging surrounding AMI threat, behavioral management, and behavioral prevention.